PENGARUH KUALITAS PELAYANAN, VARIASI PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SUPERMARKET DI PANGKALPINANG - Hasuna Eriyanti; Deri Kusmadeni (JEM Jurnal Ekonomi dan Manajemen, 2021)
Service quality is an evaluation of the customer's long-term This research entitled the correlation of service quality, product variation, price, and location on consumer purchasing decisions on the Supermarket Pangkalpinang. The population in this research were all consumers who shopped at the Supermarket in January to March 2020, while the sample in this research amounted to 275 consumers who came and shopped at the Pangkal Pinang. The variables used in this research are independent variables such as (service quality, product variation, price, and location) and the dependent variable is the purchase decision) This research used analysis tools, namely: normality test, multicollinearity, heteroskedasticity test, multiple linear regression with t-test, F test, and coefficient of determination. The results of this research stated that simultaneously service quality variables, product variations, prices, and locations have a positive and significant effect on purchasing decisions. Based on the t-test that the variable service quality, product variation, price have a positive and significant correlation on purchasing decisions while the location variable has a positive and significant correlation with purchasing decisions This research can be concluded that there is a positive and significant influence on service quality, product variations, price, and location simultaneously and partially on consumer purchasing decisions at the Supermarket Pangkalpinang, providing various types and variants of products and household need so that consumers can make product choices when shopping, be more competitive in setting product prices to be more affordable by consumers and can compete with other supermarkets, further increasing promotion through electronic media in order to introduce products and the design to consumers and researchers is further suggested to add other variables to be studied so that they can better explain what influences the dependent variable.